Phenolic Compounds and Hydroxyl Radical Scavenging Activities of Aqueous and Methanolic Extracts of Phoenix Dactylifera L Cultivar Dayri Fruits - Amir Siahpoosh; Rezvan Yazdanparast; Afsaneh Jaberkhalafian; Sara Alikazemi (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background and Objective: Nutrition and dietary patterns have been shown to have direct impact on health of the population and of selected patient groups. The antioxidant nutrition play an important role in protection against degenerative disease. The fruits of the date palm (Phoenix dactylifera) are consumed throughout the world and are an important part of the diet in Iran. The hydroxyl radical is known to cause significant damage to cellular DNA, proteins and cell wall, leading to cell death and polyphenols showed strong scavenging activity on hydroxyl radicals.Subjects and Methods: Methanol and aqueous extracts were prepared from fruits of phoenix dactilyfera by maceration method. deoxyribose method were used to evaluated hydroxyl radical scavenging capacity of herbal extract. Total phenolic content was determined by the Folin–Ciocalteu method. The flavonoids and proanthocyanidins were determined by UV spectrophotometry methods.Results: The total phenolic, flavonoids and proanthocyanidins content of methanolic and aqueous extracts were 3.77 and 17.42 mg tannic acid equivalents per g dry extract, 0.20 and 0.26 mg rutin equivalents per g dry extract and 0.12, 0.11 mg Cyanidin chloride per g dry extract, respectively. The IC50 value for methanol and aqueous extract in deoxyribose method were determined 0.76 and 0.99 mg/ml.Conclusion: Methanol and aqueous extracts exhibited hydroxyl radical scavenging activity. However, methanol extracts showed better results, but total phenolic content of aqueous extract was greater. The two extracts showed almost no differences in flavonoids and proanthocyanidins contents.